POTENSI INTERAKSI OBAT PADA PASIEN SKIZOFRENIA - Suri, Nurma; Salsabila, Lyansaputri; Adjeng, Andi Nafisah Tendri; Oktafany, Oktafany (Medula, 2024)
In the treatment of schizophrenia, antipsychotics as the main therapy are generally combined with additional therapy. Combination therapy has a risk of drug interactions. The aim of the study was to describe the potential factors that influence drug interactions. The study was conducted using observational quantitative analytic methods with a retrospective cross-sectional approach. The sample was selected by total sampling method in the medical records of inpatients at the Lampung Mental Hospital from January-December 2022. The Lexicomp software was used to identify potential drug interactions. In the 265 samples, 344 treatment profiles were obtained with a total of 1349 drugs used. Then, 1786 potential drug interactions were classified as level of risk A (0%), B (0.8%), C (80.2%), D (19%), and X (0%). There was a significant relationship between gender, length of stay, and number of drugs (p<0.05) on potential drug interaction level D (major). Multivariate analysis showed the number of drugs had the strongest relationship (p=0.000 OR=8.233) to potential drug interactions. There was a significant relationship between gender, length of stay, and number of drugs with potential drug interactions level D. The number of drugs had the strongest with potential drug interactions.